A Malay frontier unity and duality in a Sumatran kingdom - Drakard, Jane (Studies on Southeast Asia, 1990)
The way in which Malays construe ideas about authority and government is the subject of this book. Focusing upon an often-ignored section of the Malay archipelago, Barus, a small kingdom on the coast of northwest Sumatra, the author compares readings based upon the royal chronicles of Hilir and Hulu Barus. She examines the relationship between the upland and the lowland to study the character of Malay political culture in Barus